Residual state ownership and firm performance: A case of Vietnam - Manh Hoang Nguyen; Quy Thi Vo (Journal of Risk and Financial Management, 2022)
Privatization has played an important role in national economic reform in Vietnam. However, unlike other transitional countries in Central and Eastern Europe, Vietnam has chosen a partial and gradual privatization where the government still holds significant ownership in most privatized firms. Whether partial privatization can enhance privatized firms' performance or full privatization should have been implemented is a critical question that needs to be answered. This paper utilizes semiparametric regressions to study the relationship between residual state ownership and firm performance. The results indicate an inverted U relationship between state ownership and firm performance. We show that the performance of privatized firms improves with an increase in the level of state ownership until around 40%, after which the effect of state ownership on firm performance tends to decline. This demonstrates that in a transitional context, relinquishing governmental control via privatization can significantly benefit privatized firm performance. However, further reduction of state ownership may decrease the performance of privatized firms. Overall, the study contributes significantly to the growing body of evidence on the nonlinear effects of state ownership. This suggests that in the transitional context of Vietnam, due to weak corporate governance and limited protection of minority shareholders, there could be a temporary optimal position where state and private investors hold balanced ownership to simultaneously supervise operations and promote the performance of privatized firms.
Keywords: 650; firm performance; ownership structure; privatization; state ownership; Vietnam